A bio-based two-component polyurethane adhesive and preparation method thereof
Through the preparation of bio-based two-component polyurethane adhesive, the synergistic effect of castor oil, epoxy soybean oil polyol and tannin acid and other materials is solved, and the stability of polyurethane adhesive in moisture is improved. Resilience and service life, and achieve environmental protection and energy saving effects.
Patent Information
- Application Number
- CN202411554339.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-11-04
AI Technical Summary
Existing polyurethane adhesives are easily affected by moisture during use, resulting in poor storage stability and short service life. They require chemical solvents during their preparation, which is not conducive to environmental protection.
Using bio-based two-component polyurethane adhesive, the high toughness and moisture resistance bonding is formed by synergistically interacting castor oil and epoxy soybean oil polyol with tannin, lignin, fly ash and nanotitanium dioxide. Reduce the use of chemical solvents and improve the stability of the adhesive through specific preparation methods.
It significantly improves the thermal stability, tensile strength and moisture resistance of the adhesive, extends the service life, and achieves environmental protection and energy conservation.
Smart Images

Figure CN119060684B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesives, and in particular to a bio-based two-component polyurethane adhesive and a preparation method thereof. Background Art
[0002] Adhesives are very important in daily life and industry. Polyurethane molecules can form hydrogen bonds, have strong cohesive force, and have good bonding strength to various materials. They are widely used in the bonding of structural materials such as metal, rubber, wood, fiber, and plastic.
[0003] Two-component polyurethane adhesives have been widely used due to their diverse manufacturing methods and excellent product performance. The two main raw materials for synthesizing two-component polyurethanes, polyols and isocyanates, are compounds produced from petroleum and coal. With the depletion of petroleum resources and the continuous improvement of environmental protection requirements, the development of polyurethanes based on renewable resources is an inevitable trend in the polymer industry.
[0004] Currently, castor oil and soybean oil are increasingly being used in polyurethane as a renewable resource. The long chain structure of castor oil molecular chain makes the prepared polyurethane adhesive have a high viscosity, but it usually needs to add chemical solvents, which is not environmentally friendly and needs to be improved. In addition, in practical applications, the terminal NCO group in the polyurethane adhesive is very sensitive to moisture, which easily affects the storage stability of the system. In addition, the inevitable damage and breakage seriously affect the use effect of the adhesive and shorten the service life. Summary of the invention
[0005] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a bio-based two-component polyurethane adhesive and a preparation method thereof.
[0006] A bio-based two-component polyurethane adhesive comprises: a component A and a component B, wherein the mass ratio of the component A to the component B is 0.8-1.2:0.8-1.2;
[0007] The raw materials of component A include, by mass: 3-5 parts of castor oil, 3-5 parts of epoxy soybean oil polyol, 10-15 parts of isocyanate, and 1-2 parts of carboxyl-terminated polyamide-amine;
[0008] The raw materials of component B include, by mass, 1-2 parts of tannic acid, 2-4 parts of lignin, 1-2 parts of dimethylglyoxime, 5-8 parts of ricinoleyl alcohol, 3-5 parts of isocyanate, 1-2 parts of epoxy soybean oil, 1-2 parts of fly ash, and 1-2 parts of nano titanium dioxide.
[0009] Preferably, the hydroxyl value of the epoxy soybean oil polyol is 300-400 mgKOH / g.
[0010] Preferably, the isocyanate in component A is any one of isophorone diisocyanate, toluene diisocyanate and diphenylmethane diisocyanate.
[0011] Preferably, the carboxyl-terminated polyamidoamine has a generation number of 1-3.
[0012] Preferably, the fly ash particle size is 0.5 μm-1 μm.
[0013] Preferably, the isocyanate in component B is any one of toluene diisocyanate and diphenylmethane diisocyanate.
[0014] Preferably, the particle size of nano titanium dioxide is 200-300 nm.
[0015] A method for preparing a bio-based two-component polyurethane adhesive comprises the following steps:
[0016] S1. Add castor oil and epoxy soybean oil polyol into a three-necked flask, heat to 110-115°C, and dehydrate by vacuum distillation for 1-2 hours; after dehydration, cool to 65-75°C, add isocyanate, heat to 85-95°C while stirring, add carboxyl-terminated polyamide-amine, and react for 1-2 hours to obtain component A;
[0017] S2, adding tannic acid, lignin, and dimethylglyoxime to castor oil alcohol, stirring at a uniform speed, heating to 115-125°C and dehydrating by vacuum distillation for 1-2 hours, cooling to 55-65°C after dehydration, adding isocyanate, slowly heating to 75-85°C while stirring, the heating rate is 1-2°C / min, keeping the temperature for reaction for 1-2 hours, heating to 115-125°C for reaction for 1-2 hours, finally cooling to 55-65°C, adding epoxy soybean oil, lignin, fly ash, and nano titanium dioxide, stirring for 1-2 hours, and obtaining component B;
[0018] The preparation method of epoxy soybean oil polyol comprises the following steps: mixing 1-3 parts of soybean oil, 1-3 parts of hydrogen peroxide with a mass fraction of 30-35%, 0.5-1 parts of glacial acetic acid, and 0.1-0.3 parts of concentrated sulfuric acid with a mass fraction of 93-95% by weight, stirring for 6-8 hours at a stirring temperature of 55-65° C., adding 0.5-1 parts of tetrafluoroboric acid and 1-3 parts of isopropanol, stirring for 1-2 hours at a stirring temperature of 55-65° C., and obtaining epoxy soybean oil polyol;
[0019] S3. At room temperature, mix component A and component B, stir evenly, and obtain a bio-based two-component polyurethane adhesive. Beneficial Effects
[0020] In the present invention, renewable castor oil and epoxy soybean oil polyol are compounded, and then synergized with bio-based materials tannic acid and lignin, and degradable materials are used to effectively implement the concept of environmental protection. The product has little odor, does not pollute the environment, and saves energy.
[0021] In the present invention, isocyanate is added to castor oil and epoxy soybean oil polyol to form a prepolymer, which is further combined with terminal carboxyl polyamide-amine to increase the intermolecular interaction force, effectively improve the toughness and tensile strength of the adhesive, and greatly enhance the thermal stability.
[0022] Dimethylglyoxime is a type of bifunctional imine monomer with a symmetrical structure. The hydroxyl groups at both ends can undergo nucleophilic reaction with isocyanate to obtain a reversible bonding effect. Combined with the symmetrical rigid structure, it can effectively enhance the mechanical strength and stability of the adhesive, especially its excellent moisture resistance. Its inherent imine group further combines with tannic acid and lignin to form effective hydrogen bonds between molecular chains, further enhancing the moisture resistance of the adhesive.
[0023] Fly ash is a good surface modification material. Fly ash combined with lignin can form a rich microporous structure and enhance the stability of the adhesive. The epoxy structure of epoxidized soybean oil can form grafting and cross-linking with lignin to enhance the grid structure of the system. Nano-titanium dioxide is evenly dispersed in it. After curing, it can effectively enhance the tensile strength of the product, with excellent mechanical properties. At the same time, the system has good storage stability.
[0024] The invention is not only environmentally friendly, has little odor, and saves energy, but also has good moisture stability in practical applications, effectively enhances the storage stability of the system, and can reduce the occurrence of damage and breakage, thereby improving the use effect of the adhesive and extending the service life. The preparation method is simple and suitable for large-scale production and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a comparison chart of the thermal stability of the bio-based two-component polyurethane adhesives obtained using Example 5 and Comparative Examples 1-2.
[0026] Figure 2 This is a comparison chart of the water absorption rate of the bio-based two-component polyurethane adhesive obtained by Example 5 and Comparative Examples 1-2.
[0027] Figure 3 This is a comparison chart of the tensile strength of the bio-based two-component polyurethane adhesives obtained using Example 5 and Comparative Examples 1-2.
[0028] Figure 4 The stability comparison chart of the bio-based two-component polyurethane adhesive obtained by Example 5 and Comparative Examples 1-2 is shown. DETAILED DESCRIPTION
[0029] The present invention will be further explained below in conjunction with specific embodiments.
[0030] The castor oil and ricinoleyl alcohol used below were purchased from Guangzhou Taili Chemical Co., Ltd. Soybean oil was purchased from Shandong Zhonghe Chemical Co., Ltd. Tannic acid and carboxyl-terminated polyamide-amine used below were purchased from Wuhan Jilisheng Chemical Co., Ltd. Toluene diisocyanate, glacial acetic acid, concentrated sulfuric acid, hydrogen peroxide, dimethylglyoxime, tetrafluoroboric acid, and isopropanol used below were purchased from Shanghai MacLean Biochemical Technology Co., Ltd. Fly ash and nano titanium dioxide used below were purchased from Lingshou Yigao Mineral Products Processing Plant. Lignin used below was purchased from Jiaxiang Dahai Chemical Co., Ltd.
[0031] Example 1
[0032] A method for preparing a bio-based two-component polyurethane adhesive comprises the following steps:
[0033] S1. Add 3g of castor oil and 3g of epoxy soybean oil polyol into a three-necked flask, heat to 110°C and dehydrate by vacuum distillation for 2h; after dehydration, cool to 70°C, add 10g of toluene diisocyanate, heat to 90°C while stirring, add 1g of 2.0-generation carboxyl-terminated polyamide-amine, react for 2h to obtain component A;
[0034] The preparation method of epoxy soybean oil polyol comprises the following steps: 1g soybean oil, 1g hydrogen peroxide with a mass fraction of 35%, 0.5g glacial acetic acid, and 0.1g concentrated sulfuric acid with a mass fraction of 95% are mixed, stirred for 8h at a stirring temperature of 60°C, 0.5g tetrafluoroboric acid and 1g isopropanol are added, stirred for 1h at a stirring temperature of 50°C, and epoxy soybean oil polyol is obtained;
[0035] S2, add 1g tannic acid, 1g lignin, 1g dimethylglyoxime to 5g castor oil alcohol, stir at a uniform speed, heat to 120℃, dehydrate by vacuum distillation for 2h, cool to 60℃ after dehydration, add 3g toluene diisocyanate, slowly heat to 70℃ while stirring, the heating rate is 2℃ / min, keep warm for 2h, heat to 110℃ for 2h, finally cool to 60℃, add 1g epoxy soybean oil, 1g lignin, 1g fly ash with a particle size of 0.5μm, 1g nano titanium dioxide with a particle size of 200nm, stir for 2h, and obtain component B;
[0036] S3. At room temperature, component A and component B are mixed in a mass ratio of 1:1, and stirred evenly to obtain a bio-based two-component polyurethane adhesive.
[0037] Example 2
[0038] A method for preparing a bio-based two-component polyurethane adhesive comprises the following steps:
[0039] S1. Add 5g of castor oil and 5g of epoxy soybean oil polyol into a three-necked flask, heat to 110°C and dehydrate by vacuum distillation for 2h; after dehydration, cool to 70°C, add 13g of toluene diisocyanate, heat to 90°C while stirring, add 2g of 2.0-generation carboxyl-terminated polyamide-amine, react for 2h to obtain component A;
[0040] The preparation method of epoxy soybean oil polyol comprises the following steps: 3g soybean oil, 3g hydrogen peroxide with a mass fraction of 35%, 1g glacial acetic acid, and 0.3g concentrated sulfuric acid with a mass fraction of 95%, stirring for 8h at a stirring temperature of 60°C, adding 1g tetrafluoroboric acid and 3g isopropanol, stirring for 1h at a stirring temperature of 50°C, and obtaining epoxy soybean oil polyol;
[0041] S2, add 3g tannic acid, 3g lignin, 3g dimethylglyoxime to 8g castor oil alcohol, stir at a uniform speed, heat to 120℃, dehydrate by vacuum distillation for 2h, cool to 60℃ after dehydration, add 5g toluene diisocyanate, slowly heat to 70℃ while stirring, the heating rate is 2℃ / min, keep warm for 2h, heat to 110℃ for 2h, finally cool to 60℃, add 2g epoxy soybean oil, 2g lignin, 2g fly ash with a particle size of 0.5μm, 2g nano titanium dioxide with a particle size of 200nm, stir for 2h, and obtain component B;
[0042] S3. At room temperature, component A and component B are mixed in a mass ratio of 1:1, and stirred evenly to obtain a bio-based two-component polyurethane adhesive.
[0043] Example 3
[0044] A method for preparing a bio-based two-component polyurethane adhesive comprises the following steps:
[0045] S1. Add 3.1g of castor oil and 3.1g of epoxy soybean oil polyol into a three-necked flask, heat to 110°C and dehydrate by vacuum distillation for 2h; after dehydration, cool to 70°C, add 10.5g of toluene diisocyanate, heat to 90°C while stirring, add 1.1g of 2.0-generation carboxyl-terminated polyamide-amine, react for 2h to obtain component A;
[0046] The preparation method of epoxy soybean oil polyol comprises the following steps: 1.1g soybean oil, 1.1g hydrogen peroxide with a mass fraction of 35%, 0.55g glacial acetic acid, and 0.11g concentrated sulfuric acid with a mass fraction of 95% are mixed, stirred for 8h at a stirring temperature of 60°C, 0.55g tetrafluoroboric acid and 1.1g isopropanol are added, stirred for 1h at a stirring temperature of 50°C, and epoxy soybean oil polyol is obtained;
[0047] S2, add 1.1g tannic acid, 1.1g lignin, 1.1g dimethylglyoxime to 5.1 ricinoleyl alcohol, stir at a uniform speed, heat to 120°C and dehydrate by vacuum distillation for 2h, cool to 60°C after dehydration, add 3.1g toluene diisocyanate, slowly heat to 70°C while stirring, the heating rate is 2°C / min, keep warm for 2h, heat to 110°C for 2h, finally cool to 60°C, add 1.1g epoxy soybean oil, 1.1g lignin, 1.1g fly ash with a particle size of 0.5μm, 1.1g nano titanium dioxide with a particle size of 200nm, stir for 2h, and obtain component B;
[0048] S3. At room temperature, component A and component B are mixed in a mass ratio of 1:1, and stirred evenly to obtain a bio-based two-component polyurethane adhesive.
[0049] Example 4
[0050] A method for preparing a bio-based two-component polyurethane adhesive comprises the following steps:
[0051] S1. Add 4.9g of castor oil and 4.9g of epoxy soybean oil polyol into a three-necked flask, heat to 110°C and dehydrate by vacuum distillation for 2h; after dehydration, cool to 70°C, add 14.5g of toluene diisocyanate, heat to 90°C while stirring, add 1.9g of 2.0-generation carboxyl-terminated polyamide-amine, react for 2h to obtain component A;
[0052] The preparation method of epoxy soybean oil polyol comprises the following steps: 2.9g soybean oil, 2.9g hydrogen peroxide with a mass fraction of 35%, 0.95g glacial acetic acid, and 0.25g concentrated sulfuric acid with a mass fraction of 95% are mixed, stirred for 8h at a stirring temperature of 60°C, 0.95g tetrafluoroboric acid and 2.9g isopropanol are added, stirred for 1h at a stirring temperature of 50°C, and epoxy soybean oil polyol is obtained;
[0053] S2, add 1.9g tannic acid, 1.9g lignin, 1.9g dimethylglyoxime to 7.9g castor oil alcohol, stir at a uniform speed, heat to 120℃, dehydrate by vacuum distillation for 2h, cool to 60℃ after dehydration, add 4.9g toluene diisocyanate, slowly heat to 70℃ while stirring, the heating rate is 2℃ / min, keep warm for 2h, heat to 110℃ for 2h, finally cool to 60℃, add 1.9g epoxy soybean oil, 1.9g lignin, 1.9g fly ash with a particle size of 0.5μm, 1.59 nano titanium dioxide with a particle size of 200nm, stir for 2h, and obtain component B;
[0054] S3. At room temperature, component A and component B are mixed in a mass ratio of 1:1, and stirred evenly to obtain a bio-based two-component polyurethane adhesive.
[0055] Example 5
[0056] A method for preparing a bio-based two-component polyurethane adhesive comprises the following steps:
[0057] S1. Add 4g of castor oil and 4g of epoxy soybean oil polyol into a three-necked flask, heat to 110°C and dehydrate by vacuum distillation for 2h; after dehydration, cool to 70°C, add 13g of toluene diisocyanate, heat to 90°C while stirring, add 1.5g of 2.0-generation carboxyl-terminated polyamide-amine, react for 2h to obtain component A;
[0058] The preparation method of epoxy soybean oil polyol comprises the following steps: 2g soybean oil, 2g hydrogen peroxide with a mass fraction of 35%, 0.7g glacial acetic acid, and 0.2g concentrated sulfuric acid with a mass fraction of 95%, stirring for 8h at a stirring temperature of 60°C, adding 0.7g tetrafluoroboric acid and 2g isopropanol, stirring for 1h at a stirring temperature of 50°C, and obtaining epoxy soybean oil polyol;
[0059] S2, add 1.5g tannic acid, 1.5g lignin, 1.5g dimethylglyoxime to 5g castor oil alcohol, stir at a uniform speed, heat to 120℃, dehydrate by vacuum distillation for 2h, cool to 60℃ after dehydration, add 4g toluene diisocyanate, slowly heat to 70℃ while stirring, the heating rate is 2℃ / min, keep warm for 2h, heat to 110℃ for 2h, finally cool to 60℃, add 1.5g epoxy soybean oil, 1.5g lignin, 1.5g fly ash with a particle size of 0.5μm, 1.5g nano titanium dioxide with a particle size of 200nm, stir for 2h, and obtain component B;
[0060] S3. At room temperature, component A and component B are mixed in a mass ratio of 1:1, and stirred evenly to obtain a bio-based two-component polyurethane adhesive.
[0061] Comparative Example 1
[0062] A method for preparing a bio-based two-component polyurethane adhesive comprises the following steps:
[0063] S1. Add 4g of castor oil and 4g of epoxy soybean oil polyol into a three-necked flask, heat to 110°C and dehydrate by vacuum distillation for 2h; after dehydration, cool to 70°C, add 13g of toluene diisocyanate, heat to 90°C while stirring, and react for 2h to obtain component A;
[0064] The preparation method of epoxy soybean oil polyol comprises the following steps: 2g soybean oil, 2g hydrogen peroxide with a mass fraction of 35%, 0.7g glacial acetic acid, and 0.2g concentrated sulfuric acid with a mass fraction of 95%, stirring for 8h at a stirring temperature of 60°C, adding 0.7g tetrafluoroboric acid and 2g isopropanol, stirring for 1h at a stirring temperature of 50°C, and obtaining epoxy soybean oil polyol;
[0065] S2, add 1.5g tannic acid, 1.5g lignin, 1.5g dimethylglyoxime to 5g castor oil alcohol, stir at a uniform speed, heat to 120℃, dehydrate by vacuum distillation for 2h, cool to 60℃ after dehydration, add 4g toluene diisocyanate, slowly heat to 70℃ while stirring, the heating rate is 2℃ / min, keep warm for 2h, heat to 110℃ for 2h, finally cool to 60℃, add 1.5g epoxy soybean oil, 1.5g lignin, 1.5g fly ash with a particle size of 0.5μm, 1.5g nano titanium dioxide with a particle size of 200nm, stir for 2h, and obtain component B;
[0066] S3. At room temperature, component A and component B are mixed in a mass ratio of 1:1, and stirred evenly to obtain a bio-based two-component polyurethane adhesive.
[0067] Comparative Example 2
[0068] A method for preparing a bio-based two-component polyurethane adhesive comprises the following steps:
[0069] S1. Add 4g of castor oil and 4g of epoxy soybean oil polyol into a three-necked flask, heat to 110°C and dehydrate by vacuum distillation for 2h; after dehydration, cool to 70°C, add 13g of toluene diisocyanate, heat to 90°C while stirring, and react for 2h to obtain component A;
[0070] The preparation method of epoxy soybean oil polyol comprises the following steps: 2g soybean oil, 2g hydrogen peroxide with a mass fraction of 35%, 0.7g glacial acetic acid, and 0.2g concentrated sulfuric acid with a mass fraction of 95%, stirring for 8h at a stirring temperature of 60°C, adding 0.7g tetrafluoroboric acid and 2g isopropanol, stirring for 1h at a stirring temperature of 50°C, and obtaining epoxy soybean oil polyol;
[0071] S2, add 1.5g tannic acid, 1.5g lignin, 1.5g polyethyleneimine to 5g castor oil alcohol, stir at a uniform speed, heat to 120℃, dehydrate by vacuum distillation for 2h, cool to 60℃ after dehydration, add 4g toluene diisocyanate, slowly heat to 70℃ while stirring, the heating rate is 2℃ / min, keep warm for 2h, heat to 110℃ for 2h, finally cool to 60℃, add 1.5g epoxy soybean oil, 1.5g lignin, 1.5g fly ash with a particle size of 0.5μm, 1.5g nano titanium dioxide with a particle size of 200nm, stir for 2h, and obtain component B;
[0072] S3. At room temperature, component A and component B are mixed in a mass ratio of 1:1, and stirred evenly to obtain a bio-based two-component polyurethane adhesive.
[0073] test
[0074] The bio-based two-component polyurethane adhesives prepared in Example 5 and Comparative Examples 1-2 were cured for 8 hours and divided into Example 5 group and Comparative Examples 1-2 group, and the following tests were performed respectively.
[0075] Thermal stability test
[0076] The TG method was used for the determination. A 10 mg sample was placed under nitrogen and heated from 50°C to 650°C at a rate of 10°C / min, with a flow rate of 50 mL / min. Before the test, the samples were dried at 60°C for 12 hours. The mass was recorded at every 200°C to obtain the heat loss rate. The test results are as follows: Figure 1 As shown, the heat loss rate of Example 5 is the smallest at different temperatures, which is better than that of Comparative Examples 1-2.
[0077] Water absorption test
[0078] In a humidity environment of 98% RH, 5 15mm×15mm square bio-based two-component polyurethane adhesive films were placed in a 24-well cell culture plate and dried to a constant weight, and then placed in a humidity environment of 98% RH until the mass reached a stable state.
[0079] Water absorption (W) = (m1-m0) / m0
[0080] Where: m1 is the weight of the adhesive film after absorbing water (kg); m0 is the initial constant weight (kg). Figure 2 As shown, the water absorption rate of Example 5 group is the smallest, which is better than that of Comparative Examples 1-2 groups.
[0081] Tensile strength test
[0082] The tensile properties of bio-based two-component polyurethane adhesive materials were tested using a WSM electronic universal tensile testing machine. The sample was cut into a dumbbell shape. The measurement conditions were: sensor 500N, tensile rate 100mm / min, sample size 20mm×2mm×5mm. The tensile rate was 2mm / min, and the tensile strength was measured. The test results are as follows: Figure 3 As shown, the tensile strength of Example 5 is the largest, which is better than that of Comparative Examples 1-2.
[0083] Stability test
[0084] Sand the surface of a 10cm×10cm×60cm iron block with sandpaper and clean the surface with acetone. Apply a homemade two-component epoxy-modified polyurethane adhesive on the inside. After the surface is dry for 1 hour, a peel strength test is performed. The peel strength test is performed every two months after continuous storage for 6 months to obtain the peel strength loss rate. The test results are as follows: Figure 4As shown, the loss rate of Example 5 group was the smallest at different time periods, which was better than that of Comparative Examples 1-2 groups.
[0085] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A bio-based two-component polyurethane adhesive, characterized in that: include: The mass ratio of component A to component B is 0.8-1.2:0.8-1.2; The raw materials of component A include, by mass: 3-5 parts of castor oil, 3-5 parts of epoxy soybean oil polyol, 10-15 parts of isocyanate, and 1-2 parts of carboxyl-terminated polyamide-amine; The raw materials of component B include, by mass, 1-2 parts of tannic acid, 2-4 parts of lignin, 1-2 parts of dimethylglyoxime, 5-8 parts of ricinoleyl alcohol, 3-5 parts of isocyanate, 1-2 parts of epoxy soybean oil, 1-2 parts of fly ash, and 1-2 parts of nano titanium dioxide.
2. The bio-based two-component polyurethane adhesive according to claim 1, characterized in that: The hydroxyl value of epoxy soybean oil polyol is 300-400 mgKOH / g.
3. The bio-based two-component polyurethane adhesive according to claim 1, characterized in that: The isocyanate in component A is any one of isophorone diisocyanate, toluene diisocyanate and diphenylmethane diisocyanate.
4. The bio-based two-component polyurethane adhesive according to claim 1, characterized in that: The carboxyl-terminated polyamide-amine has a generation number of 1-3.
5. The bio-based two-component polyurethane adhesive according to claim 1, characterized in that: The particle size of fly ash is 0.5μm-1μm.
6. The bio-based two-component polyurethane adhesive according to claim 1, characterized in that: The isocyanate in component B is any one of toluene diisocyanate and diphenylmethane diisocyanate.
7. The bio-based two-component polyurethane adhesive according to claim 1, characterized in that: The particle size of nano titanium dioxide is 200-300nm.
8. A method for preparing a bio-based two-component polyurethane adhesive according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Add castor oil and epoxy soybean oil polyol into a three-necked flask, heat to 110-115°C, and dehydrate by vacuum distillation for 1-2 hours; after dehydration, cool to 65-75°C, add isocyanate, heat to 85-95°C while stirring, add carboxyl-terminated polyamide-amine, and react for 1-2 hours to obtain component A; S2, adding tannic acid, lignin, and dimethylglyoxime to castor oil alcohol, stirring at a uniform speed, heating to 115-125°C and dehydrating by vacuum distillation for 1-2 hours, cooling to 55-65°C after dehydration, adding isocyanate, slowly heating to 75-85°C while stirring, the heating rate is 1-2°C / min, keeping the temperature for reaction for 1-2 hours, heating to 115-125°C for reaction for 1-2 hours, finally cooling to 55-65°C, adding epoxy soybean oil, lignin, fly ash, and nano titanium dioxide, stirring for 1-2 hours, and obtaining component B; S3. At room temperature, mix component A and component B, stir evenly, and obtain a bio-based two-component polyurethane adhesive.
Citation Information
Patent Citations
Solvent-free polyurethane adhesive with high initial viscosity and preparation method thereof
CN105176475A
Preparation method of water-based adhesive for labels
CN116589963A
Cited By
Targeted self-repairing polyurethane sealant and preparation method thereof
CN121343544A